Pollen and Vertebrates of the Early Neogene Haughton Formation, Devon Island, Arctic Canada - Whitlock, Cathy; Dawson, Mary R. (ARCTIC, 1990)
The Haughton Formation of northern Devon Island, arctic Canada, consists of sediments deposited in a lake that filled a large impact crater, which has been dated as early Miocene. The fossiliferous sediments contain a rich assemblage of pollen, some plant megafossils, and the only known early Neogene arctic vertebrates. Common pollen types are Pinus, Ericales, Corylus-type, Betula, and Alnus. Picea, Larix, Cupressaceae, and Ulmus/Zelkova also occur. These taxa, rarer hardwoods, and spores allow a vegetational reconstruction of a mixed conifer-hardwood forest. Climatic conditions were cool temperate with maritime influences. Vertebrates, including trout, smelt, swan, and four mammal genera, lend support to the climatic interpretation, and they also suggest considerable endemism for the mammals. The Haughton flora appears to be bracketed temporally by floras from various parts of the widely distributed Beaufort Formation.